2022
DOI: 10.1002/ehf2.13799
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac allograft vasculopathy and donor age affecting permanent pacemaker implantation after heart transplantation

Abstract: AimsThe need for permanent pacemakers (PMs) after heart transplantation (HT) is increasing. The aim was to determine the influence of cardiac allograft vasculopathy (CAV), donor age, and other risk factors on PM implantations early and late after HT and its effect on survival. Methods and results A retrospective, single-centre study was performed including HTs from 1984 to July 2018. Early PM was defined as PM implantation ≤90 days and late PM as PM > 90 days. Risk factors for PM and survival after PM were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…We found no survival difference between pacemaker and non-pacemaker groups at 1 year post-transplantation, consistent with several published single-center studies [ 7 , 8 , 11 , 12 , 13 ]. Of note, Wellmann et al excluded early mortality within 3 months post transplantation, because the authors believed that patients who died early never had the chance to receive a pacemaker, and noted no long-term survival benefit [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no survival difference between pacemaker and non-pacemaker groups at 1 year post-transplantation, consistent with several published single-center studies [ 7 , 8 , 11 , 12 , 13 ]. Of note, Wellmann et al excluded early mortality within 3 months post transplantation, because the authors believed that patients who died early never had the chance to receive a pacemaker, and noted no long-term survival benefit [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…As years pass, the era effect that we have observed yields a lower incidence of implantation; this may mask true differences in mortality. Prior studies have also demonstrated differential survival in early vs. late post-operative pacemaker implantation, but the limitations of our dataset prevented us from making these comparisons [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, early permanent pacemaker (PPM) implantation has been increasingly utilized to treat persistent bradycardia following bradyarrhythmias occurring after transplantation, mainly due to the increasing age of suitable donors in Europe, especially in the Netherlands (1).…”
mentioning
confidence: 99%
“…The prevalence of both theophylline uses (12 patients before and 61 patients after 2000) as well as need of a PPM increased significantly along with increasing donor ages in the past two decades. Figure 1 shows the percentage of theophylline use vs. permanent pacemaker implant at discharge before and after the year 2000, a year in which the baseline immunosuppressive treatment and donor ages changed significantly in our center (1,4). There were no significant correlations with successful vs. not successful treatment regarding the recipient age (mean 46.6 ± 14.0 vs. 43.8±14.9 years), donor age (mean 40.6 ± 14.7 vs. 42.5 ± 12.7 years), gender, preoperative use of amiodaron (53 vs. 67%), or underlying heart diseases (28 vs. 33 % ischemic heart diseases).…”
mentioning
confidence: 99%
See 1 more Smart Citation